Evaluation of serum CTLA-4 levels in patients with HBs Ag (-)/HBc IgG (+)/Hbs Ab (+): Across sectional study in the Najaf Government - Baneen Abdul Hadi Jalaout Al-Hamdani; Saif Jabbar Yasir Al-Mayah (مجلة الكوفة الطبية)
Background: Hepatitis B virus is a virus that attacks the liver, leading to viral hepatitis, cirrhosis, and liver cancer in humans. The diagnostic markers for hepatitis B, anti-HBc IgG and anti-HBs Ab, are widely recognized. A cytotoxic T-lymphocyte antigen-4 called CTLA-4 is an immune checkpoint protein that stops the HBV infection from spreading. It accomplishes this by serving as a sort of inhibitory receptor, restricting the quantity of damage that an acute infection can cause to the hepatocyte and enhancing the infection's capacity to remain in the body throughout a chronic illness. Aim of the study: The study aims to evaluate serum CTLA-4 levels in individuals with HBsAg-negative, HBc IgG-positive, and HBs-positive Ab and explore the association between these findings and the existence and development of HBV infection.  Patients and methods: A cross-sectional study was performed from July to October 2023. The serum was taken from 200 individuals, all of whom were tested by using an immunochromatographic assay for HBsAb, HBsAg, HBcAb, HBeAg, and HBeAb and also by using an ELISA technique for CTLA-4 and HBc IgG. The statistical analysis was conducted by using SPSS version 26. Results: Serum CTLA-4 level positively correlated with HBsAg-negative, HBc IgG-positive, and HBs-positive patient antibodies (p = 0.000), serum HBs Ab positivity (P = 0.000), and total HBc Ab positivity (P<0.001), all linked to the amount of CTLA-4. Serum HBe Ab negativity was not linked to CTLA-4 (p = 0.181). Conclusions: Elevated serum CTLA-4 level in patients with HBs Ag-negative, HBc IgG-positive, and HBs-positive Ab.